Technologies for setting goals as a part of the leadership competence of a vocational education teacherʺ - Bakatanova , V.; Bulynin, V. (Problems of Engineer-Pedagogical Education, 2023)
The article elucidates the characteristics of leadership and leadership qualities, delves into the definitions of leadership and leadership competence, conducts an analysis of prominent global goal-setting methodologies, and explores their potential applicability in the training of future vocational education teachers. Furthermore, the article introduces the MIPTAR goal-setting technology developed by the authors, accompanied by a theoretical rationale for its implementation in vocational education. Contemporary societal trends accentuate individual initiative, autonomous engagement, selforganization, and self-regulation. The question of acquiring organizational and leadership skills in the youth environment, with the aim of addressing substantial societal challenges, remains pertinent. The cultivation of leaders in a progressive society is not an arbitrary progression but rather a systematic and proactive approach to nurturing personal and leadership qualities within individuals. Leadership is an effective source of any transformations within organizations and communities. It serves as an effective mechanism for the advancement and evolution of these entities. Profound societal changes throughout history have invariably been the consequence of the initiatives of leaders who have reshaped social dynamics, as exemplified by figures such as B.M. Khmelnytskyi, M. Gandhi, M.L. King, N. Mandella, Lee Kuan Yew, and others, or innovators like T. Edison, F. Porsche, G. Ford, S. Jobs, and others. The role of leaders is most clearly manifested in changing periods of the development of society, times of socio-economic transformations, instability of the world around. A vocational education teacher, responsible for the training of skilled workforce, occupies the role of a leader, thus performing one of the key roles in the development of the economy and industry in our country. Such individuals function as organizers of both educational and production processes. In order to execute their responsibilities effectively, vocational education teachers must cultivate leadership qualities and proficiently manage their life and professional priorities. As experts and leaders within their domain, they require an efficient goal-setting methodology that accommodates the specific requirements of their profession and aligns with a well-defined goal-setting algorithm. The potential avenues for further research in this direction encompass enhancing the training of prospective vocational education teachers and the application of the algorithm proposed in this article for goal-setting in higher education.